Development of failure evaluation method for BWR Lower head in severe accident; - Creep damage evaluation based on thermal-hydraulics and structural analyses - - Jinya KATSUYAMA (The Japan Society of Mechanical Engineers, 2016)
In existing severe accident codes such as MELCOR and THALES2, rupture of reactor pressure vessel (RPV) by relocated molten core is judged using simple models such as temperature and/or stress criteria. However, it is difficult to assess rupture behavior of the lower head of RPV in boiling-water-type nuclear power plants due to severe accident like Fukushima Daiichi. One reason is that boiling water reactors (BWRs) have geometrically complicated structure with a lot of penetrations. Another one is that BWR lower head is composed of various types of materials of RPV, weld-overlay cladding, control rod guide tubes, stub tubes, welds, etc. Therefore, we have been developing an analysis method to predict time and location of RPV lower head rupture of BWRs considering creep damage mechanisms based on coupled analysis of three-dimensional thermal-hydraulics (TH) and thermal-elastic-plastic-creep analyses. The detailed three-dimensional model of RPV lower head with control rod guide tubes, stub tubes, and welds are constructed. TH analysis is performed to obtain three-dimensional temperature distribution in relocated debris. Using TH analysis results, structural analysis is carried out to evaluate creep damage distributions using four types of damage criterions of “considere”, strain, Kachanov, and Larson-Miller-parameter (LMP) criteria. Creep damage evaluation based on Kachanov and LMP models is made by using experimentally determined parameters. From comparison of damage criterions, it is shown that failure regions of BWR lower head are only penetrations under simulated conditions, although there is a large difference in failure time.